2007
DOI: 10.1103/physrevd.76.075016
|View full text |Cite
|
Sign up to set email alerts
|

Four generations and Higgs physics

Abstract: In the light of the LHC, we revisit the implications of a fourth generation of chiral matter. We identify a specific ensemble of particle masses and mixings that are in agreement with all current experimental bounds as well as minimize the contributions to electroweak precision observables. Higgs masses between 115-315 (115-750) GeV are allowed by electroweak precision data at the 68% and 95% CL. Within this parameter space, there are dramatic effects on Higgs phenomenology: production rates are enhanced, weak… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
496
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 389 publications
(523 citation statements)
references
References 70 publications
27
496
0
Order By: Relevance
“…However they also contribute to the ρ parameter and Kribs et. al. showed that an acceptable combined fit to precision electroweak data can be achieved, for example, with a mass splitting of about 50 GeV between fourth generation quarks in the mass range 350 − 700 GeV [2]. See also see the earlier work in [3].…”
Section: I Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However they also contribute to the ρ parameter and Kribs et. al. showed that an acceptable combined fit to precision electroweak data can be achieved, for example, with a mass splitting of about 50 GeV between fourth generation quarks in the mass range 350 − 700 GeV [2]. See also see the earlier work in [3].…”
Section: I Introductionmentioning
confidence: 99%
“…Such bound states come with different color, spin and flavor quantum numbers. Since the fourth generation Yukawa coupling, λ q ′ , is large we include all perturbative corrections to the potential between the heavy quark and antiquark of order λ 2 q ′ Nc/16π 2 where Nc is the number of colors, as well as relativistic corrections suppressed by (v/c) 2 . We find that the lightest fourth generation quark masses for which a bound state exists for color octet states.…”
mentioning
confidence: 99%
“…So a large multiplicity of extra generations is required to enhance Bσ in the γγ channel by an order of magnitude, as can be seen in can be found in Refs. [14,15].…”
Section: Enhancing Diphoton Resonancesmentioning
confidence: 99%
“…The second one claimes that the status of the fourth generation is subtle [1]. This approach illustrates that the experimental results make some constrains on the fourth generation parameters, i. e., masses(fourth neutrino mass has to be greater than the half of the Z boson mass) and mixing [2]. While an unstable neutrino with mass of 50 GeV is ruled out by LEP II bounds, the stable one may be ruled out by dark matter direct search experiments [2].…”
Section: Introductionmentioning
confidence: 99%
“…This approach illustrates that the experimental results make some constrains on the fourth generation parameters, i. e., masses(fourth neutrino mass has to be greater than the half of the Z boson mass) and mixing [2]. While an unstable neutrino with mass of 50 GeV is ruled out by LEP II bounds, the stable one may be ruled out by dark matter direct search experiments [2]. Many authors who support the existence of fourth generation studied those effects in various areas, for instance, Higgs and neutrino physics, cosmology and dark matter [3]- [7].…”
Section: Introductionmentioning
confidence: 99%